2012
DOI: 10.1111/j.1095-8649.2012.03375.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary preference and feeding selectivity of common dragonet Callionymus lyra in U.K.

Abstract: The gut contents of 90 individuals of common dragonet Callionymus lyra were analysed, of which 76 contained prey, along with 100 corresponding benthic grab samples in order to assess the diet of C. lyra in relation to the availability of its prey in the environment. Forty-five prey taxa were identified in the diet from 350 potential prey taxa identified in the environment. Calculation of the index of relative importance (I(RI)) found the main food components were crustaceans (%I(RI) = 86·3), mostly the porcela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…The positive effect of Calanus nauplii abundance in the current and preceding year on the proportion of Callionymidae is in line with this. Callionymidae are opportunistic feeders so may utilise abundant Calanus nauplii when they are available (Griffin et al 2012). This link may also underpin the negative relationship between prey richness and Calanus nauplii, whereby good feeding conditions for Callionymidae may result in shags reducing the consumption of other non-sandeel prey, leading to lower diet diversity.…”
Section: Annual Effectsmentioning
confidence: 99%
“…The positive effect of Calanus nauplii abundance in the current and preceding year on the proportion of Callionymidae is in line with this. Callionymidae are opportunistic feeders so may utilise abundant Calanus nauplii when they are available (Griffin et al 2012). This link may also underpin the negative relationship between prey richness and Calanus nauplii, whereby good feeding conditions for Callionymidae may result in shags reducing the consumption of other non-sandeel prey, leading to lower diet diversity.…”
Section: Annual Effectsmentioning
confidence: 99%
“…Therefore, the higher percentage of prey consumed during summer can be explained by an increase in crustacean availability from April to August. The ability to vary feeding preference in response to prey availability is quite common in marine vertebrates (Varo et al 2011;Griffin et al 2012;Matić-Skoko et al 2014) and in several invertebrate phyla, such as gorgonians (Leal et al 2014), nemerteans (Caplins et al 2012), and echinoderms (Chiantore et al 2002). Soler-Membrives et al (2011) found a very similar trend to ours in the trophodynamics of the pycnogonid Ammothella longipes, which appears to be carnivorous during spring and early summer, but prefers detritus when prey availability diminishes during winter.…”
Section: Discussionmentioning
confidence: 98%
“…Although long‐lines and gill nets are generally considered as highly selective gears (Stobart et al, and references therein), they also catch numerous by‐catch species. Therefore, the high intensity of fishing in the area (Sbrescia et al, , ) could have also had more subtle direct and indirect effects on spatial patterns of the whole fish assemblage (Farina et al, ; Griffin, Pearce, & Handy, ; Marriott, Latchford, & McCarthy, ; Sala & Lucchetti, ), including changes in small‐scale heterogeneity.…”
Section: Discussionmentioning
confidence: 99%